PENGGUNAAN MULTIMEDIA UNTUK PEMBELAJARAN KOSAKATA BAHASA INGGRIS DI SEKOLAH DASAR - Jauhara, Dadan; Iskhak, Iskhak (Jurnal Intisabi, 2025)
This article investigated the students’ perception on the implementing of multimedia which was designed to teach vocabulary related to animals to young learners of English as a foreign language (EFL). This study has taken place in one state primary school in Kota Banjar. In this study, 16 students of primary school were asked to respond the questionnaire based on their experience in learning vocabularies using multimedia. This study employed qualitative research under a case study. The data collected from students’ checklist by using questionnaire, class observation, and interview. Questionnaires were analyzed in term of students’ perception. The data were analyzed in ongoing process. The results indicated that the participants have a positive perception on the implementation of multimedia in teaching vocabularies of animals. Image and sound that are produced by the video help them in understanding the words. They can mentioned animals’ name based on the sound their produced, and they can identify animals’ name based on its features, such as size of the body, skin colour, animals’ habitats, and physical shape (e.g. nose, eyes, legs, wings, etc.).